Analisis Kontras Spekel menggunakan LSI (Laser Speckel Imaging) untuk Mendeteksi Formalin pada Tomat (Lycopersicum Esculentum Mill): Neneng Fitrya, Sandra, Harmadi - Neneng Fitrya, Neneng Fitrya; Sandra, Sandra; Harmadi, Harmadi (Jurnal Fisika dan Aplikasinya, 2025)
Has been performed formaldehyde detection on tomatoes using LSI (Laser Spekcle Imaging) method. LSI system consists of three main components, wichh is a laser as a light source, a sample and a light detector. The imaging of speckle pattern with LSI method detects changes in the intensity of the laser speckle that is scattered by the sample, and analyzed as speckle contrast. Speckle pattern was analyzed using ImageJ software and obtained characterization gray level intensity distribution histogram. Change in contrast value of the speckle pattern of tomatoes can be used to distinguish the tomatoes with and without formaldehyde. Irradiation is carried out on tomato before and after the tomato soaked with various concentration of formaldehyde solution 2%, 3%, 4%, 5% and the variation immersion time for 15 minutes and 30 minutes. In general, the speckle contrast correlation with formaldehyde in tomatoes, showed that formaldehyde was detected by speckle contrast changes in tomatoes. The higher concentration of formaldehyde and immersion time, speckle contrast value will get smaller.